Relationships between socio-political and character conflicts in selected novels of Ian McEwan - Abbasiyannejad, Mina (2013)
The present study examines and analyses the relationship between conflicts in the macrocosm (world and society) and conflicts in the microcosm (individuals). While exploring cultural and political conflicts, and pinpointing the major and influential causes of problems, it scrutinizes the individuals’ lives to recognize the existing conflicts between characters through the identification and interpretation of signs, symbols and metaphors. The selected stories, for this study are On Chesil Beach, Atonement, The Innocent and Black Dogs. Using theories of social stratification and sexual politics as a framework, the study reveals the omnipresent effect of societal power on people’s relationships. Semiotics as a tool assists the reader in identifying any signs related to the conflicts in order to recognize meanings hidden beyond words. The selected novels are tales of incompatibility, generated by economic inequality, sexual restrictions or political power. On Chesil Beach and Atonement are both stories marked by unequal relationships both from class and sexuality. On the other hand, The Innocent and Black Dogs are riddled with party (political) domination and sexual conflicts in society. Moreover, political challenges to the power in society give rise to other diverse conflicts,e.g. the struggle among the victors of the Second World War during the Cold War that followed. In the same vein, sexual politics demonstrates that sex is not merely biological act but has political implications. The study shows the multi-dimensional aspects of sex,demonstrating how women can be oppressed in economic and political terms. The oppressive period before the sexual revolution, generates conflicts among people particularly the young, which is shown in various ways in the novels. McEwan demonstrates how conflicts between humans (microcosm) are metaphors for world and social turmoil (macrocosm). The study also shows McEwan’s concern with issues such as war, class and sexual conflicts in his novels which mirror his personal life. The findings of this study indicate that economic inequalities and political conflicts along with sexual restrictions permeate the affluent and powerful who are in a position to dominate the impoverished and the powerless, who seem to be easy targets for oppression.